The effect of disclosing identities in a socially incentivized public good game - Britta Butz; Christine Harbring (Games, 2021)
We investigate whether revealing the identities in a public good game that includes a donation incentive leads to higher contributions to the public good. Previous evidence suggests that contributions to a public good increase significantly when these take place in public. Also, the amount of money given in charitable donations seems to be sensitive to the revealing of identities. Using a laboratory experiment, we implement a 20% donation share that is dependent on participants' contributions to a public good. The donation is either costless (because it is financed by the experimenter) or deducted from a team's contributions. In both settings, we explore whether informing participants that group members' identities will be disclosed at the end of the experiment leads to higher contributions to the public good. Non-parametric statistics indicate that when donations are costly for the participants, the announcement of subsequent identity disclosure results in significantly higher contributions in the second half of the repeated public good game. In contrast, revealing identities in settings with costless donations reduces contributions to the public good significantly. The regression results indicate that conditional cooperators might be one subgroup driving these results.
Keywords: 330; anonymity; charitable giving; cooperation; donations; laboratory experiment; pro-sociality; public good game; social dilemma; team incentives